2019
DOI: 10.1101/724674
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Computational mapping of the differentially expressed gene-lncRNA pairs present at the root nodule developmental stages of Arachis hypogaea

Abstract: RNA-sequencing (RNA-seq) data analysis of the different stages of root nodules formation in peanut Arachis hypogaea investigate the genetic features. Genes related to the root nodules formations in this plant are extensively studied [1] [2] [3] [4] [5], but less information is present for their relations with long noncoding RNAs (lncRNAs). Bioinformatics techniques are utilised here to identify the novel lncRNAs present in the publically available RNA-seq data reported [6] for the different stages of root nodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…They are potential regulatory molecules which can modulate the gene expression at transcriptional, post-transcriptional, epigenetic levels to influence various biological and metabolic processes that enable plants to tolerate various abiotic and biotic stresses (Kim and Sung 2012 ). Recent studies have suggested that lncRNAs can influence the expression of target genes through cis- or trans-regulation and can be cleaved by miRNAs to generate siRNAs to silence the target genes (Wang et al 2018 , Fu et al 2019 , Rizvi and Dhusia 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…They are potential regulatory molecules which can modulate the gene expression at transcriptional, post-transcriptional, epigenetic levels to influence various biological and metabolic processes that enable plants to tolerate various abiotic and biotic stresses (Kim and Sung 2012 ). Recent studies have suggested that lncRNAs can influence the expression of target genes through cis- or trans-regulation and can be cleaved by miRNAs to generate siRNAs to silence the target genes (Wang et al 2018 , Fu et al 2019 , Rizvi and Dhusia 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In plants, the standard for target mimics is much stricter than that in animals, and the positive position of the sequence must not contain paired bases (resulting in protrusions). Recent studies have revealed that lncRNAs can alter the expression of target genes through cis-or trans-regulation and can be cleaved by miRNAs to generate siRNAs to silence target genes Fu et al, 2019;Rizvi and Dhusia, 2019). Additionally, some natural antisense lncRNAs help regulate target gene expression (Swiezewski et al, 2009;Huanca-Mamani et al, 2018).…”
Section: Introductionmentioning
confidence: 99%